Targeting Persons With or At High Risk for Chronic Obstructive Pulmonary Disease by State-based Surveillance. (2nd November 2015) - Pleasants, Roy A.; Heidari, Khosrow; Wheaton, Anne G.; Ohar, Jill A.; Strange, Charlie; Croft, Janet B.; Liao, Winston; Mannino, David M.; Kraft, Monica
Abstract: The Behavioral Risk Factor Surveillance System (BRFSS) survey is used to estimate chronic obstructive pulmonary disease (COPD) prevalence and could be expanded to describe respiratory symptoms in the general population and to characterize persons with or at high risk for the disease. Tobacco duration and respiratory symptom questions were added to the 2012 South Carolina BRFSS. Data concerning sociodemographics, chronic illnesses, health behaviors, and respiratory symptoms were collected in 9438 adults ≥ 35 years-old. Respondents were categorized as having COPD, high risk, or low risk for the disease. High risk was defined as no self-reported COPD, ≥ 10 years' tobacco use, and ≥ 1 respiratory symptom (frequent productive cough or shortness of breath (SOB), or breathing problems affecting activities). Prevalence of self-reported and high-risk COPD were 9.1% and 8.0%, respectively. Overall, 17.3%, 10.6%, and 5.2% of all respondents reported activities limited by breathing problems, frequent productive cough, and frequent SOB, respectively. The high-risk group was more likely than the COPD group to report a productive cough and breathing problems limiting activities as well as being current smokers, male, and African-American. Health impairment was more severe in the COPD than the high-risk group, and both were worse than the low-risk group. Conclusions : Persons at high risk for COPD share many, but not all, of the characteristics of persons diagnosed with the disease. Additional questions addressing smoking duration and respiratory symptoms in the BRFSS identifies groups at high risk for having or developing COPD who may benefit from smoking cessation and case-finding interventions.